Pulmonary oedema without critical increase in left atrial pressure in acute myocardial infarction. Issue 6292 (5th September 1981) - Timmis, A D; Fowler, M B; Burwood, R J; Gishen, P; Vincent, R; Chamberlain, D A
Abstract : Twelve patients with acute myocardial infarction and radiological evidence of pulmonary oedema were observed in whom the left atrial pressure, measured indirectly as pulmonary artery end-diastolic pressure, was not critically increased (range 5-12 mm Hg with reference to sternal angle). Eight of the patients had been treated with frusemide, but only six had responded: hence in at least half of the series diuresis could not account for the anomalous finding. Six patients with low cardiac output were given infusions to expand plasma volume. Appreciable increments in mean values for cardiac index (1.6 to 2.0 1/min/m2), stroke index (18 to 23 ml/beat/m2), mean arterial pressure (65 to 86 mm Hg), and pulmonary artery end-diastolic pressure (8 to 15 mm Hg) were recorded. This group, and the remaining six patients with higher cardiac output, survived to leave hospital. Delay in radiographic clearing after a fall of left atrial pressure was a possible explanation for the relatively low pulmonary artery end-diastolic pressures, especially in the patients treated successfully with diuretics. Other mechanisms, such as alterations in pulmonary vascular permeability, might also have contributed to the syndrome. Pulmonary oedema without a critical increase in the left atrial pressure is unusual in acute myocardial infarction but the therapeutic implications are important. Withdrawal;of diuretics may be indicated, and in some cases expansion of plasma volume may lead to striking clinical improvement.